EFEKTIFITAS KEBIJAKAN MONETER TERHADAP INFLASI DI INDONESIA - Andi Rachman Setyawan (Jurnal Ekonomi Pembangunan, 2010)
The purpose of this research is to determine the effect of monetary policy through the discount rate and reserve requirement by the Central Bank as well as the previous inflation towards the inflation rate, and to investigate the effectiveness of monetary policy through the discount rate and reserve requirement as well as the previous inflation in influencing the rate of inflation. The data that is used to determine the discount rate and reserve requirements affect inflation in Indonesia is using multiple linear regression model with the approach of the Partial Adjustment Model (PAM) and statistical (partial, simultaneous tests and the coefficient of determination) as well as classical assumption or econometrics (test normality, linearity, autocorrelation, multicolinearity and heteroscedasticity). From these results, it is known that monetary policy from the first quarter 1985 to first quarter 2010 was still less effective direct influence on inflation, this can be known from a partial test done even though the relationship of monetary policy is consistent with monetarist theory.